A Modular Approach for a Family of Ground Mobile Robots. (22nd July 2013) - Quaglia, Giuseppe; Oderio, Riccardo; Bruzzone, Luca; Razzoli, Roberto
This paper deals with Epi.q, a family of mobile robots whose main characteristic is a wheel-legged hybrid locomotion. These multi-purpose robots can be successfully exploited for security and surveillance tasks. The document presents state of the art security robotics, the Epi.q mechanical architecture, the concept behind the robot driving unit, three prototypes and the design of a new one.